Measurement of the diffractive longitudinal structure function FDL at HERA - Aaron, Francisc Dionisie; Pirumov, Hayk; Sauter, Michel David; Schöning, André; Schultz-Coulon, Hans-Christian (The European physical journal. C, Particles and fields, 2011)
First measurements are presented of the diffractive cross section σ ep→eXY at centre-of-mass energies √s of 225 and 252GeV, together with a precise new measurement at √s of 319GeV, using data taken with the H1 detector in the years 2006 and 2007. Together with previous H1 data at √s of 301GeV, the measurements are used to extract the diffractive longitudinal structure function FDL in the range of photon virtualities 4.0≤Q2≤44.0GeV2 and fractional proton longitudinal momentum loss 5×10−4≤x ℙ≤3×10−3. The measured FDL is compared with leading twist predictions based on diffractive parton densities extracted in NLO QCD fits to previous measurements of diffractive Deep-Inelastic Scattering and with a model which additionally includes a higher twist contribution derived from a colour dipole approach. The ratio of the diffractive cross section induced by longitudinally polarised photons to that for transversely polarised photons is extracted and compared with the analogous quantity for inclusive Deep-Inelastic Scattering.
H1 Collaboration*: F.D. Aaron, H. Pirumov, M. Sauter, A. Schoening, H.-C. Schultz-Coulon [und 199 weitere Personen]
Im Titel ist der Buchstabe D hochgestellt sowie der Buchstabe L tiefgestellt
Gesehen am 22.02.2022